Molecular Characterization of Novel Totivirus-Like Double-Stranded RNAs from Puccinia striiformis f. sp. tritici, the Causal Agent of Wheat Stripe Rust - Zheng, Li; Lu, Xia; Liang, Xiaofei; Jiang, Shuchang; Zhao, Jing; Zhan, Gangming; Liu, Peng; Wu, Jianhui; Kang, Zhensheng (Frontiers in Microbiology, 2017)
Characterization of newly isolated mycoviruses may contribute to understanding of the evolution and diversity of viruses. The obligate biotrophic fungus Puccinia striiformis f. sp. tritici causes stripe (yellow) rust disease on wheat worldwide. Here, a deep sequencing approach was used to analyze the double-stranded RNA (dsRNA) mycoviruses isolated from field-collected P. striiformis samples in China. Datebase searches showed the presence of at least four totivirus-like sequences, termed Puccinia striiformis virus 1 to 4 (PsV1 to 4). All of these identified sequences contained two overlapping open reading frames (ORFs) which encode a putative coat protein (CP) and an RNA-dependent RNA polymerase (RdRp) showing similar structures to members of the genus Totivirus. Each PsV contained a -1 ribosomal frameshifting region with a slippery site and a pseudoknot structure in the overlapped regions of these ORFs, indicating that the RdRp is translated as a CP-RdRp fusion. Phylogenetic analyses based on RdRp and CP suggested that these novel viruses belong to the genus Totivirus in the family Totiviridae. The presences of these PsVs were further validated by transmission electron microscope (TEM) and RT-PCR. Taken together, our results first demonstrate the presence of diverse, novel totiviruses in the P. striiformis field populations.